2015
DOI: 10.1016/j.jacc.2015.03.553
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Benefits of Reducing Indoor Particles of Outdoor Origin

Abstract: Background Indoor exposure to fine particulate matter (PM2.5) from outdoor sources is a major health concern, especially in highly polluted developing countries, such as China. Few studies have evaluated the effectiveness of indoor air purification on the improvement of cardiopulmonary health in these areas. Objectives To evaluate whether a short-term indoor air purifier intervention improves cardiopulmonary health. Methods We conducted a randomized double-blind crossover trial among 35 healthy college stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
120
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(131 citation statements)
references
References 28 publications
9
120
1
1
Order By: Relevance
“…In this randomized, double-blind, crossover trial, we found marked changes in serum metabolites, including hormones, glucose, amino acids, and lipids, in association with higher PM 2.5 exposure. Consistent with previous publications from us 29 and other groups in China, 7,30 we also observed increases in blood pressure and levels of biomarkers of inflammation and oxidative stress in relation to higher PM 2.5 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this randomized, double-blind, crossover trial, we found marked changes in serum metabolites, including hormones, glucose, amino acids, and lipids, in association with higher PM 2.5 exposure. Consistent with previous publications from us 29 and other groups in China, 7,30 we also observed increases in blood pressure and levels of biomarkers of inflammation and oxidative stress in relation to higher PM 2.5 .…”
Section: Discussionsupporting
confidence: 93%
“…In this randomized, double-blind, crossover trial, we found marked changes in serum metabolites, including hormones, glucose, amino acids, and lipids, in association with higher PM 2.5 exposure. Consistent with previous publications from us 29 and other groups in China, 7,30 we also observed increases in blood pressure and levels of biomarkers of inflammation and oxidative stress in relation to higher PM 2.5 .Results from this clinical trial suggest that the human central nervous system reacts to changes in PM exposures. We observed increases in glucocorticoids, ACTH, and CRH in relation to higher PM exposure, suggesting activation of the hypothalamus-pituitary-adrenal (HPA) axis.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In fact, there is evidence that adverse mechanisms associated with PM 2.5 exposure include elevated inflammation and enhanced thrombosis as well as vascular dysfunction and autonomic imbalance 1, 2. A recent randomized, double‐blind, crossover intervention study of healthy adults from Shanghai, China, for example, reported that substantial reductions in PM 2.5 exposures for 48 hours from air purification resulted in cardiopulmonary benefits, including decreases in several circulating inflammatory and thrombogenic biomarkers and lower systolic and diastolic blood pressure 27. Given these implied adverse mechanisms, in the context of universal definition and clinical classification of MI,28 these results suggest that there are differential effects of PM 2.5 exposures on different types of MI.…”
Section: Discussionmentioning
confidence: 99%